Learning References in Printed and Online Mediums For Academic Purposes - Ting, Su Hie; Fatimah, Puteh (Procedia - Social and Behavioral Sciences, 2012)
The study examine the University students' preference for printed or online mediums for learning reference in an English for Academic Purposes course. Students were taught reference in a module on reading skills using printed materials before they were introduced to the MyLinE online resources on references. The two cohesive devices focused on were anaphoric and cataphoric reference. For the survey, students filled in a questionnaire which focused on the comprehensibility of the explanations, usefulness and difficulty level of the exercises, and their preference for the printed or online language learning media. The results indicated that the students were divided in their preference for the printed module and the MyLine online resources. Students who were in favour of the printed module cited the advantage of personalised face-to-face two-way interaction with their lecturers as crucial in assisting their comprehension of the subject matter whereas students who preferred the online language learning medium cited convenience of referring to other online resources and the interest factor.